ANALYSIS OF ADLER PERSONALITY THEORY IN NOVEL A PRISONER OF BIRTH - Rapi, Ahmad Adam; Nur, Riola Haya (Journal of English Literature and Linguistic Studies, 2025)
In this study, researcher analyzed Alfred Adler personality theory in a literary novel. The researcher analyzed two problems of Adlerian Strategies namely: (1) What is the conflict that is presented in the novel A Prisoner of Birth? (2) How is the conflict developed based on Adler Theory? The literary novel entitled A Prisoner of Birth that is a work of Jeffrey Archer. The method that is used in this research is qualitative method and psychological approach. This method and approach is used in this research because it is considered more suitable in finding and examining social problems that occur in humans. Based on findings at chapter 4, there are 2 aspects of Adlerian Strategies which is inferiority complex that have 4 types and superiority complex that have 3 types that found in novel.